Modeling Forced Imbibition Processes and the Associated Seismic Attenuation in Heterogeneous Porous Rocks - Solazzi, Santiago Gabriel (2017)
Quantifying seismic attenuation during laboratory imbibition experiments can provide useful information towards the use of seismic waves for monitoring injection and extraction of fluids in the Earth's crust. However, a deeper understanding of the physical causes producing the observed attenuation is needed for this purpose. In this work, we analyze seismic attenuation due to mesoscopic wave-induced fluid flow (WIFF) produced by realistic fluid distributions representative of imbibition experiments. To do so, we first perform two-phase flow simulations in a heterogeneous rock sample to emulate a forced imbibition experiment. We then select a sub-sample of the considered rock containing the resulting time-dependent saturation fields, and apply a numerical upscaling procedure to compute the associated seismic attenuation. By exploring both saturation distributions and seismic attenuation we observe that two manifestations of WIFF arise during imbibition experiments: the first one is produced by the compressibility contrast associated with the saturation front, whereas the second one is due to the presence of patches containing very high amounts of water that are located behind the saturation front. We demonstrate that while the former process is expected to play a significant role in the case of high injection rates, which are associated with viscous-dominated imbibition processes, the latter becomes predominant during capillary-dominated processes, that is, for relatively low injection rates. We conclude that this kind of joint numerical analysis constitutes a useful tool for improving our understanding of the physical mechanisms producing seismic attenuation during laboratory imbibition experiments.